(untitled) (Bangladesh Journal of Botany, 2025)
Based on distribution data of 140 sites and 10 environmental factors of Ranunculus ternatus Thunb. The MaxEnt model and geographic information system (GIS) were used to predict potentially suitable habitats of the species. The results showed that the area under the curve (AUC) value of the area under the receiver operation characteristic curve (ROC) was 0.92, indicating that the model prediction results were reliable. The highly suitable areas of Ranunculus ternatus Thunb in China are mainly concentrated in the provinces of the Yangtze River Basin including the southern Henan province central and southern Anhui province, southern Jiangsu province, Shanghai, eastern and northern Zhejiang province northern Jiangxi province southern Hubei province and central Hunan province, part of Chongqing and north of Taiwan, covering an area of about 3.39 of China’s land area. The dominant environmental factors affecting the distribution of Ranunculus ternatus Thunb were related to precipitation and temperature, including precipitation in March, seasonal changes of precipitation, isotherm and standard deviation of seasonal changes in temperature. These results are consistent with the actual distribution and biological characteristics of Ranunculus ternatus Thunb , and can provide a reference for its promotion and planting. Bangladesh J. Bot. 54(3): 791-796, 2025 (September) Special